ERROR ANALYSIS ON USING SIMPLE PAST TENSE IN WRITING RECOUNT TEXT AT THE EIGHTH GRADE OF SMP BINA BERSAUDARA 1 MEDAN - rahmawati wati (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2019)
This research was discussed about error analysis on using simple past tense in writing recount text. The objective of the study were to find out the types of errors, to describe the students error, and to find out the difficulties of students on using simple past tense in writing recount text. The approach of this research is qualitative research. The instrument of this research were writing a recount text, choose the right sentence or word from a recount text, and interview. The subjects of this research were 25 students of eighth grade students of SMP BINA BERSAUDARA 1 Medan. The data was collected by students’ answer sheet. The collected data was identified, calssified, analysed and interpreted based on the types of errors using theory corder’s were 237 errors. The finding revealed that there are 4 types of errors. They are omission, addition,selection, and ordering. Selection was the dominant errors with 151 errors (64%), followed by ordering with 37 errors (16%), addition with 31 errors (13%), and the last was addition wirh 18 errors (7%). Based on the data analysis above, the most of students’ errors was selection and the least of students’ errors was addition.